Association of plasma visfatin with risk of colorectal cancer: An observational study of Chinese patients. Issue 1 (2nd August 2013) - Chen, Mingwei; Wang, Youming; Li, Yongxiang; Zhao, Lili; Ye, Shuai; Wang, Shenyi; Yu, Changjun; Xie, Huijuan
Abstract: Aim: To investigate the association between plasma visfatin levels and risk of early and advanced colorectal cancer (CRC). Methods: In total, 358 CRC patients and 286 controls were enrolled. According to the T factor of the TNM system. cancer patients were divided into two subgroups: early and advanced cancer. Levels of visfatin, anthropometric and metabolic parameters, which were classified as low, medium, and high, based on the tertile distributions in the control group, were determined. Results: The visfatin levels in patients with advanced and early cancer were higher than in controls (least significant difference test, P = 0.004 and 0.013, respectively). The patients in the highest tertile of visfatin concentration presented significantly higher odds for early and advanced CRC, adjusted for potential confounding factors (odds ratio 3.37; 95% CI, 1.93–8.37; P = 0.011; odds ratio 2.38; 95% CI: 1.82–8.35; P = 0.015, respectively). The visfatin level correlated significantly with waist:hip ratio ( P < 0.05 for all) among case and control participants. Plasma visfatin levels in early and advanced CRC yielded a receiver operating characteristic curve area of 72 and 86%, respectively. The optimal sensitivity and specificity were 73% and 57% in discriminating between early CRC and normal controls while they were 76% and 68% in discriminating between advanced CRC and normal controls. Conclusion: An increased level of visfatin was a strong risk factor for both early and advanced CRC in Chinese patients. Plasma visfatin levels might be a potential biomarker for CRC detection.